'Reverse-payment' patent settlement agreements: non-cash value transfers are not immune from competition law scrutiny. (19th January 2018) - Lawrance, Sophie; Bond, Edwin
Abstract: The authors: Sophie Lawrance is a Partner and Edwin Bond is an Associate in Bristows LLP's competition team. They regularly advise clients on complex issues arising where competition law and IP law intersect, and have particular experience of working with businesses in the technology and pharmaceutical sectors. The team handles both non-contentious and contentious work, the latter in a variety of fora including the English and EU courts. This article: In the last decade, competition authorities in the US and the EU have paid particular attention to 'reverse payment' patent settlement agreements in the pharmaceutical sector. In the US, both the Federal Trade Commission and the courts have grappled with a specific species of patent settlement agreement which involves a commitment by the patent owner not to launch an authorised generic version of its brand-name drug (known as a 'no-AG agreement'). In King Drug v SmithKline Beecham, the US Court of Appeals for the Third Circuit held that non-cash value transfer settlements generally and no-AG agreements in particular should be subject to the same rule-of-reason analysis as transfers of cash. In the EU, no-AG agreements have received much less attention from the competition authorities and the courts. In the current state of evolution of the law, however, it seems clear that non-cash value transfers are no more immune from scrutiny under EU competition law than they are under the US competition rules. Nevertheless, the different legal framework means that effects on competition should not be assumed.